Time Efficiency Calculation of the Nutmeg (Myristica fragrans Houtt.) Mifra®22 Pericarp Grater - Elpin E. Alom; Frangky J. Paat; Tommy B. Ogie; Ronny Nangoi; Joachim Y. E. Oessoe (Jurnal Agroekoteknologi Terapan, 2022)
The purpose of this study was to obtain production time efficiency on the MIFRA®22 nutmeg pericarp grater. Research at the Agricultural Engineering Laboratory, Faculty of Agriculture, UNSRAT Manado. The research period starts from March 25 to April 30, 2022. This study was designed using a completely randomized design (CRD) method with 3 treatments and 4 replications. Treatment consists of: 1). The interval of grating duration is 10 minutes, 2). The interval of grating duration is 15 minutes, and 3). The interval of grating duration is 20 minutes. Each time interval is repeated 4 times. Grated using a nutmeg pericarp grater MIFRA®22 roller grater with 250 blades. Data were tabulated and analyzed using One-way ANOVA Confidence Interval 95% and continued with 5% BNJ test (Pongoh et al, 2022). The results of calculating the best efficiency were obtained in the treatment duration of 15 minutes with an average grating time of 81.5 seconds. The calculation of the pericarp weight of grated nutmeg resulted in an average weight of 435 grams. Calculation of the weight of the flesh of nutmeg is not shredded with an average weight of 65 grams. The percentage efficiency of grating time with an average of 84.92%.